A questionable character - Barrett, Lorna (Barrett, Lorna. Booktown mystery., 2023)
"The murder of a local contractor may be the final nail in the coffin for Tricia Miles in the latest entry to Lorna Barrett's New York Times bestselling Booktown series. It's a busy summer in Booktown. Contractor Jim Stark is in great demand: he's overseeing a number of projects, including Angelica Miles's newly constructed building on Main Street, finishing up the new brew pub, and gutting a stone mansion off Main Street that Angelica bought to be the world headquarters for Nigela Ricita Asssociates. Located on one of the side streets, it'll house office space where her marketing staff and the rest of the NR Associates clerical personnel will work. Tricia Miles and Angelica arrive at the mansion before their workday to see how the construction is going. They find the place unlocked and Stark's right-hand man, Sanjay Arya, dead--bludgeoned to death. The loss of the contractor's top man threatens all the projects in the works, which would effectively ruin the expensive marketing plan that the Chamber of Commerce has been working. Is Jim a suspect? (He'd be stupid to kill the person he depends on to keep the projects going.) But Stark also thinks his wife, who was very chummy with Sanjay, might have been cheating on him with the second-in-command, making him a likely suspect. Once again Tricia finds herself in the middle of a murder investigation, but can she find the killer before he or she has the chance to bring the hammer down?"--